Pemanfaatan Lempung sebagai Penyumbang Partikel Tersuspensi dalam Pengolahan Air Limbah Rumah Tangga - Ningsih, Erlinda; Nisa, Nur Ihda Farikhatin; Alfania, Vicha; Salsabila, Kintan Rizky; Eksalia, Lina; Najuba, Maulidina Aulia; Romadahnia, Clarisa Novela (Jurnal Teknologi Lingkungan Lahan Basah, 2023)
Household waste is waste originating from kitchens, bathrooms, laundry, former household industrial waste and human waste. Household waste is generated every day and the amount is too much to match the population and has the potential to pollute and poison the environment. Management of household waste in order to reduce the impact on the environment and public health. The method used in this study is a batch system through a coagulation-flocculation process. The first step is by adding chlorine and lime to reduce the color intensity, then clay to increase the content of suspended particles, and adding alum as a coagulant. Coagulant added based on variations and followed by fast stirring at 200 rpm and slow stirring to enlarge the floc. The ratio of coagulant addition is 2:0.3:1:1 and 2:0.5:1:1. Based on the results of the analysis, it was found that domestic waste that has been treated has 2 parameters that comply with regulations, namely BOD and pH. The added coagulant has a less significant impact on the turbidity, TSS, and color parameters. Meanwhile, the BOD and pH values decreased